(untitled) (Linguist, 2026)
This research theoretically focuses on describing and analyzing the speech act theory of both Austin and Searle. The study begins with the foundational stage of the theory in Austin’s work, highlighting the key distinctions underlying the complete speech act, and then addresses the criteria that render a speech act performative. Regarding the theory’s development with Searle, it underwent a series of modifications, most notably Searle’s adoption of the performative act as the core of speech act theory, his revision of the conditions for a successful speech act, and finally, his distinct classification of performative acts compared to that of his teacher, Austin.In the applied aspect of the research, we aimed to examine one of the criminal acts committed through language, namely the act of threat in legal contexts. Within the framework of pragmatic linguistics, a threat is defined as a speech act that carries connotations of intimidation, fear, or coercion for the addressee, whether explicitly or implicitly. In the legal domain, however, a threat is considered a crime punishable by law when it meets the fundamental conditions that render it an unlawful act.This paper focuses on studying and analyzing expressions involving the speech act of threat in a specific context by exploring the methods employed by the speaker to execute this act. It clarifies the distinction between the speech act of threat and that of warning, and outlines the circumstances under which it can be inferred that the speaker has seriously committed the act of threat.